The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.jedc.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A Hotelling model with a ceiling on the stock of pollution

Abstract: Environmental agreements such as the Kyoto Protocol aim to stabilize the amount of carbon in the atmosphere, which is mainly caused by the burning of nonrenewable resources such as coal. We characterize the solution to the textbook Hotelling model when there is a ceiling on the stock of emissions. We consider both increasing and decreasing demand for energy. We show that when the ceiling is binding, both the low-cost nonrenewable resource and the high-cost renewable resource may be used jointly. A key implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 21 publications
2
55
1
5
Order By: Relevance
“…This model has been extensively applied in resource economics (Dasgupta and Heal 1974) to derive the optimal price path of an exhaustible resource over time. Given that a carbon budget is conceptually similar to an exhaustible resource, it has hence been applied to derive optimal emission prices and in general optimal policies with stock pollutants (Tahvonen 1997, Chakravorty et al 2006, Gollier 2018, Dietz and Venmans 2019 Then, we use a numerical DP-IAM with a richer process detail including different carbon dioxide removal (CDR) assumptions, which have been shown to be crucial for low temperature targets (Tavoni and Socolow 2013, IPCC 2018, van Vuuren et al 2018, Obersteiner et al 2018, allowing us to quantify the effects of discounting under alternative assumptions about negative emissions.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been extensively applied in resource economics (Dasgupta and Heal 1974) to derive the optimal price path of an exhaustible resource over time. Given that a carbon budget is conceptually similar to an exhaustible resource, it has hence been applied to derive optimal emission prices and in general optimal policies with stock pollutants (Tahvonen 1997, Chakravorty et al 2006, Gollier 2018, Dietz and Venmans 2019 Then, we use a numerical DP-IAM with a richer process detail including different carbon dioxide removal (CDR) assumptions, which have been shown to be crucial for low temperature targets (Tavoni and Socolow 2013, IPCC 2018, van Vuuren et al 2018, Obersteiner et al 2018, allowing us to quantify the effects of discounting under alternative assumptions about negative emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Following an approach pioneered by Chakravorty et al (2006), we assume that pollution does not harm directly welfare but be crossed over some pollution concentration threshold, the earth climate conditions would become catastrophic. Let G(t) ≡ S(t) + Z(t) be the global pollution stock level at time t and G be the catastrophic threshold.…”
Section: The Modelmentioning
confidence: 99%
“…5 To avoid the catastrophe, the objective of an environmental policy is to maintain the atmospheric carbon concentration below the critical level. This approach has been extensively explored by Chakravorty et al (2006Chakravorty et al ( , 2008. Amigues et al (2011) have shown that taking into account damages increasing with the pollution stock, for stocks smaller than the critical threshold, does not change the main qualitative properties of the optimal paths.…”
Section: Introductionmentioning
confidence: 99%
“…Chakravorty et al. () find that a ceiling on the stock of pollution can give rise to simultaneous use without a flow dependent fossil fuel extraction cost function.…”
mentioning
confidence: 99%